Fatigue strength to the different type of specimens and shapes - 'Umayr Hasan, Sohaimi (2007)
The fatigue properties of metals are quite structure-sensitive. This project will study the endurance of some materials such as Aluminum, Mild Steel, Brass and Copper using fatigue testing method. Raw materials are first being cut using Horizontal Bandsaw machine. Then, they are form to the desired geometry using CNC Lathe machine. After specimens are prepared, experiment is performed using Fatigue Tester. The purpose of this study wants to know the fatigue limit that a materials can endured. Result shows that mild steel has the highest load cycles that it can endured and follows with brass, aluminum and copper. The specimens' distance to the load also influenced the endurance limit of a specimen.